Improvement of Aspects of Subjective Sleep Quality of Healthy Volunteers by Ingestion of Porcine Placental Extract: A Randomized Cross-Over Pilot Study - Nagase, Mahiko; Watanabe, Chiharu; Kitanohara, Masataka; Nishiya, Masashi; Okada, Takao; Ohishi, Masami; Komatsu, Yasuhiko (Frontiers in Nutrition, 2020)
Objectives: This study assessed the effects of oral porcine placental extract (PPE) on sleep quality of healthy volunteers not satisfied with their sleep. Design: This study used a randomized, placebo-controlled, double-blind, cross-over clinical pilot study. Setting: This study was conducted under an outpatient multicenter setting in Japan. Interventions: A total of 20 healthy Japanese volunteers aged between 28 and 73, whose Pittsburgh Sleep Quality Index global scores were between 6 and 10, successfully completed the study. At first, PPE at 300 mg/kg or placebo was ingested for 2 weeks. Then, after a 2-week washout period, each group ingested under a cross-over setting the opposite sample (placebo or PPE) for another 2 weeks. Main Outcome Measures: Objective measurement of the sleep made with an activity tracker and subjective measurements of sleep quality by use of St. Mary's Hospital Sleep Questionnaire were done just before and after the administration time slots. Results: No effect of PPE on the sleep length was observed. Several measures in the subjective St. Mary's Hospital Sleep Questionnaire, i.e., changes in Q5 (sleep depth) and Q9 (sleep wellness) between pre- and post-ingestions, were significantly different between groups in the direction of improvement of subjective sleep quality in the PPE group. Conclusions: Although oral PPE at 300 mg/day for 2 weeks did not affect the length of sleep itself, it significantly improved several measures of subjective sleep quality. These results suggest that PPE might be a way to improve sleep quality without hypnotic drugs. Clinical Trial Registration:www.umin.ac.jp/ctr/, identifier: UMIN000026468.